Liquid-liquid crystalline phase separation of evolving amyloid fibrils - Paride Azzari; Raffaele Mezzenga (Physical Review Research, 2023)
We study the conditions necessary for the onset of liquid-liquid crystalline phase separation (LLCPS) in a system of dynamically evolving amyloid fibrils whose kinetics is controlled by nucleation, growth and fragmentation. In the case of thin, rigid rods, the volume fraction does not influence the emergence of LLCPS, which is always possible. Beyond the constraints imposed by rigid rods, for semiflexible fibrils, LLCPS stems out instead from a trade-off between the contour and persistence length. Fibrils fragmentation affects LLCPS in a similar manner by delaying the concentration needed for LLCPS onset.